2009
DOI: 10.1016/j.bpj.2009.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Improved Model of Fluorescence Recovery Expands the Application of Multiphoton Fluorescence Recovery after Photobleaching in Vivo

Abstract: Multiphoton fluorescence recovery after photobleaching is a well-established microscopy technique used to measure the diffusion of macromolecules in biological systems. We have developed an improved model of the fluorescence recovery that includes the effects of convective flows within a system. We demonstrate the validity of this two-component diffusion-convection model through in vitro experimentation in systems with known diffusion coefficients and known flow speeds, and show that the diffusion-convection m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 43 publications
0
48
0
Order By: Relevance
“…Multiphoton fluorescence after photobleaching (MP-FRAP) of injected FITC-BSA was used to calculate the lymph viscosity and speed [46]. It was found that there was no difference in lymph viscosity between WT, expanding or collapsed PLN mice.…”
Section: Measurement Of Lymph Node Pressure Lymphatic Pumping Prementioning
confidence: 99%
“…Multiphoton fluorescence after photobleaching (MP-FRAP) of injected FITC-BSA was used to calculate the lymph viscosity and speed [46]. It was found that there was no difference in lymph viscosity between WT, expanding or collapsed PLN mice.…”
Section: Measurement Of Lymph Node Pressure Lymphatic Pumping Prementioning
confidence: 99%
“…Due to the nonlinear excitation in multiphoton-based photobleaching experiments, only the fluorophore within the focal spot is photobleached and the photobleaching profile yields a well-defined 3D geometry 6, 13, 16 . Moreover, due to the deeper penetration of multiphoton imaging 12 , multiphoton fluorescence recovery after photobleaching (MP-FRAP) techniques can be applied to thick samples with large light scattering 5, 26 . However, current 3D MP-FRAP models and techniques focus on the isotropic diffusion measurements due to the primary application involving the study of protein mobilities within intracellular structures.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the shape of the fluorescence recovery curve changes, and so must the mathematical model describing the recovery. By introducing a simple coordinate shift into the derivation of the equation immediately above, the new derivation yields (Sullivan et al 2009)…”
Section: Introductionmentioning
confidence: 99%
“…All other variables are defined as above. With this “diffusion-convection” model, accurate values for the diffusion coefficient can be obtained even under the influence of moderate flows, defined by a dimensionless speed parameter, v s = v(w r /8D) ≤ 3 (Fig.3) (Sullivan et al 2009). …”
Section: Introductionmentioning
confidence: 99%